A 58‐year‐old man with B‐cell chronic lymphocytic leukemia and multiple strokes. (30th July 2021) - Magrinelli, Francesca; Mariotto, Sara; Nadali, Gianpaolo; Todeschini, Giuseppe; Lanzafame, Massimiliano; Cavallaro, Tiziana; Monaco, Salvatore; Ferrari, Sergio
Abstract : A 58‐year‐old male with B‐cell chronic lymphocytic leukemia presented with fever, chest pain, and acute‐onset neurological deficits suggestive of multiple strokes (A). Brain autopsy revealed softening areas in the brain parenchyma (B, C) corresponding to extensive necrosis (D) caused by neuroinvasion by Aspergillus hyphae (E, F) necrosis (D) caused by neuroinvasion by Aspergillus hyphae (E, F).